Herbal medicine as adjunctive therapy with antidepressants for post-stroke depression: a systematic review and network meta-analysis of randomized controlled trials - Zhang, Jian; Ming, Shuping; Chen, Xiaoming; Zhang, Teng; Qian, Hongyu; Peng, Shixiong; Ding, Yanbing (Frontiers in Pharmacology, 2023)
Background: Herbal medicine can provide adjunctive therapy for adults with post-stroke depression. This study summarizes the latest evidence regarding the harms and benefits of herbal antidepressants. Methods: The literature searched from the Cochrane Library (using the OVID platform), Embase, PubMed, the China National Knowledge Infrastructure (CNKI), the Wan Fang Data Knowledge Service Platform, and the China Scientific Journal Database (VIP) from their inception to 18 August 2021, for randomized controlled trials of herbal medicine in adults with post-stroke depression, were included in this systematic review and network meta-analysis. The search was updated on 1 December 2022. To summarize the evidence, the frequentist random-effect network meta-analyses were conducted. To categorize interventions, rate the certainty of the evidence, and present the findings, the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) frameworks were carried out. The registration number of this study on PROSPERO website is CRD 42021273956. Findings: Of 1132 citations identified from the search, 51 randomized clinical trials, totaling 4,507 participants, met the inclusion criteria for this study. For response rate, Shugan Jieyu capsule (SJC) plus selective serotonin reuptake inhibitors (SSRI), Jie-Yu Pills plus SSRI, and Wuling capsule plus SSRI were shown to be among the most effective with moderate certainty of evidence (RR: 1·45, 95%CI: 1·23 to 1·7; RR: 1·35, 95%CI: 1·09 to 1·68; RR: 1·32, 95%CI: 1·09 to 1·59). In terms of mean changes in Hamilton depression scale (HAMD) score after the completion of treatment, Wuling capsule plus Hypericum and Wuling capsule plus SSRI were found to be among the most effective in reducing symptoms of depression with moderate certainty of evidence (MD: 10·12, 95%CI: −17·25 to −2·99; MD: −3·81, 95%CI: −6·19 to −1·42). The network meta-analysis (NMA) showed that SJC may be a safer intervention than SSRI in terms of both total gastrointestinal and total nervous system events with moderate certainty of evidence (RR:0.34, 95%CI:0.18, 0.62 and RR: 0.11, 95%CI: 0.03, 0.35, respectively). Interpretation: SJC plus SSRI, Jie-Yu Pills plus SSRI, and Wuling capsule plus SSRI were among the most effective in terms of HAMD score reduction response rates. Low to very low certainty of evidence revealed no increased risk of gastrointestinal and nervous system events. Systematic Review Registration:https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=273956; Identifier: CRD42021273956.